Self-reported attitudes of elite athletes towards doping: Differences between type of sport - Alaranta, A.; Alaranta, H.; Holmila, J.; Palmu, P.; Pietilä, K.; Helenius, I. (International Journal of Sports Medicine, 2006)
Although athletes' beliefs and values are known to influence whether or not an athlete will use banned drugs, little is known about the athletes' beliefs and attitudes in different sports. The aim of this study was to clarify the beliefs and attitudes of elite athletes towards banned substances and methods in sports. A total of 446 athletes (response rate 90.3 %; 446/494) financially supported by the National Finnish Olympic Committee completed a structured questionnaire during their national team camps in 2002. More than 90 % of the athletes reported to believe that banned substances and methods have performance enhancing effects, and 30 % reported that they personally know an athlete who uses banned substances. Of the male athletes 35 %, and 23 % of females reported they personally know an athlete using banned substances. A total of 15 % of the athletes reported that they had been offered banned substances: 21 % of the speed and power athletes, 14 % of the team sport athletes and of the athletes in motor skills demanding events, and 10 % of the endurance athletes. Stimulants were the most often offered substance group (to 7 % of all the athletes) followed by anabolic steroids (4 %). Subjects who regarded doping as a minor health risk seemed to be more often associated with doping users than those regarding doping as a significant health risk. Athletes in different sports have a different approach to doping. Risk of doping appears to be highest in speed and power sports and lowest in motor skills demanding sports. Males are at higher risk than females. Controlling doping only by tests is not sufficient. A profound change in the attitudes is needed, which should be monitored repeatedly.